Thermal-mechanical loading on three-dimensional printing lattice structure - Tay, Ban Lee (Nanyang Technological University, 2023)
Lattice structures are utilized and produced for diverse industries with varying objectives. Numerous investigations have been conducted to assess the mechanical and thermal capacities of lattice structures. These findings are essential in improving the design and functionality of such structures for their specific purposes. A prior study was carried out to analyze the mechanical load responses of three distinct types of lattice structures, namely the Octet-Truss lattice structure, Body-Centred Cubic (BCC) and Face-Centred Cubic (FCC). The study's findings indicated that the Octet Truss Lattice structure exhibited superior compressive properties compared to the BCC and FCC structures under varying loading conditions and different parameters such as structural radius and unit lattice cell length. Also, the Octet Truss Lattice structure demonstrated the highest thermal conductivity across increasing heat flux levels.